Between transnationalism and assimilation: Polish parents' upbringing approaches in Belfast, Northern Ireland. (4th May 2017) - Kempny-Mazur, Marta
ABSTRACT: Drawing on one-year-long ethnographic study this paper deals with parenting strategies of Polish migrants in Belfast, Northern Ireland. It first provides a general overview of the context for migration in Northern Ireland. It then introduces the theoretical framework for this study, drawing on scholarly debates on acculturation and indicating the gaps in scholarship on Polish migration. Following this, upbringing strategies of Polish parents are examined with particular focus on questions of transnationalism and assimilation. Next, the dynamic and processual nature of these strategies is emphasized. Methods used in this paper are in-depth interviews and participant observation.